Comparison of analytical methods for the fatty acid profile in ewes’ milk - Soares, Évelyn Silva de Melo; Ferreira Ítavo, Camila Celeste Brandão; Ítavo, Luís Carlos Vinhas; dos Santos, Geraldo Tadeu; Nazário, Carlos Eduardo Domingues; Soares, Israel Shekinah Souza; Cavalheiro, Leandro Fontoura (PLOS ONE, 2022)
Studies comparing methodologies for fatty acids are very important, since they can influence the quality and final quantification of the lipid fraction. Objective—to compare different extraction methods for total lipids and to evaluate the effect of these methodologies on the quantitative composition of fatty acids in milk of lactating ewes raised in tropical pastures. The methodologies used were simple direct transesterification, using the HPLC grade organic solvent n-hexane, Bligh; Dyer (cold extraction, extracting mixture proportions 5, 10, and 15 mL in a ratio of 2:1:1 (v/v/v) of chloroform-methanol-water). The fatty acid methyl esters were separated by gas chromatography coupled with a flame ionization detector (GC-FID). The results show that there was no significant difference (p <0.05) in the total lipid content between the extraction methods. However, the Bligh’s method; Dyer obtained the best yield of lipids to be extracted from ewe’s milk, since the volume with 15 mL of the extraction solution was able to identify 87% of the chromatographic peaks. It was also observed that ewe’s milk has a higher percentage of palmitic, stearic and oleic fatty acids, with percentages of 20.1%, 15.5% and 33.1%, respectively. Therefore, an extraction mixture with a volume of 15 mL used in this study may be an alternative to perform the extraction of milk fat from high lactating ewes in tropical pastures as a routine method, as it expresses the best lipid content of this food.